Graphene-porphyrin single-molecule transistors. Issue 31 (17th July 2015) - Mol, Jan A.; Lau, Chit Siong; Lewis, Wilfred J. M.; Sadeghi, Hatef; Roche, Cecile; Cnossen, Arjen; Warner, Jamie H.; Lambert, Colin J.; Anderson, Harry L.; Briggs, G. Andrew D.
Abstract : We demonstrate a robust graphene-molecule-graphene transistor architecture. Abstract : We demonstrate a robust graphene-molecule-graphene transistor architecture. We observe remarkably reproducible single electron charging, which we attribute to insensitivity of the molecular junction to the atomic configuration of the graphene electrodes. The stability of the graphene electrodes allow for high-bias transport spectroscopy and the observation of multiple redox states at room-temperature.